Structure of overall race time among Russian triathletes-juniors - Nemtsev, O. B.; Kozlov, I. S.; Pevneva, M. V.; Nemtseva, N. A.; Kucherenko, Ju. O. (2017)
The objective of this study was the investigation of correlations between the overall race results and swimming (750 m), cycling (20 km) and running (5 km) split times and also between the split results in these components in triathlon in Russian among the triathletes-juniors. The authors have analyzed the results of 42 male (age 17.6±1.1) athletes following the protocols of the Russian Junior Triathlon Championship 2016. Spearman's correlation coefficient was used to accomplish the purpose of the study. The have been found the following correlations: the strong correlation between the overall race time and running split time (? = 0.865), medium correlation between the overall race time and swimming (? = 0.629) and cycling split times (? = 0.542). Correlation between running and swimming (? = 0.343) and running and cycling (? = 0.306) split times was poorly observed. No correlation was found between swimming and cycling split times (? = 0.093).